2022
DOI: 10.21521/mw.6698
|View full text |Cite
|
Sign up to set email alerts
|

Association of NRAMP1 gene polymorphism with the productive traits of the Ukrainian Large White pig

Abstract: The study aimed to determine the influence of NRAMP1 gene polymorphisms on the pig's productive traits. Genomic DNA was isolated from blood samples (n=50) from pigs of the Ukrainian Large White breed. Genotyping was performed at NRAMP1 loci at positions 72 and 364 (AvaII) SNP and 176 and 334 (HinfI) SNP, counting from the beginning of the amplified fragment 536 bp. Polymorphism was found at the last two these loci. For NRAMP1HinfI 334 SNP, the frequency of the allele T was 1.9 times as high as that of the alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…These breeds are threatened by high rates of consanguinity and the resulting loss of biodiversity (Llambí et al, 2020). At the same time, local breeds of pigs are distinguished by valuable qualities primarily related to their resistance to diseases and high adaptability (Vashchenko et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These breeds are threatened by high rates of consanguinity and the resulting loss of biodiversity (Llambí et al, 2020). At the same time, local breeds of pigs are distinguished by valuable qualities primarily related to their resistance to diseases and high adaptability (Vashchenko et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…He et al (2013) found a strong correlation between chicken resistance to S. enteritidis and a mutation at the NRAMP1 gene's g.24101991A>T location. Several studies have shown that the NRAMP1 gene is associated with tuberculosis in human populations (Li et al, 2022); Salmonella disease in rats (Janiszewski et al, 2021); Tuberculosis disease in cows (Yuan et al, 2021); The nature of pig immunity (Vashchenko et al, 2022); Salmonellosis and virus infections in goats and sheep (Worku, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary analysis of QTL genes' polymorphism is important for the expansion and development of methodological approaches to increasing the productivity of pigs (Buske et al, 2006;Bovo et al, 2020;Vashchenko et al, 2022). In the future, these approaches can be implemented on a large herd.…”
Section: Introductionmentioning
confidence: 99%